FROM THE HISTORY OF POLITICAL CAMPAIGNS OF THE 20-30S OF THE XX CENTURY. - Shoirakhon Kambarova; Jahongir Olimov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The short period, which passed from the first days of the establishment of the Soviet system to the end of the 30s of the 20th century, brought great splendor to the head of the Uzbek people. The article examines the process of repressions and political "cleanups"of this period by the authors, reflects on the conducted political campaigns, their types and images.